Latex agglutination test for rapid detection of antibodies to infectious hematopoietic necrosis virus of salmon - M. L. Doronin; V. A. Pylnov; S. S. Rybakov (Ветеринария сегодня)
Latex-agglutination preparations were produced for detection of antibodies to infectious hematopoietic necrosis virus of salmon with analytical sensitivity of 0,9 цд/ті. While testing 40 blood samples using latex-agglutination test the diagnostic sensitivity and specificity were 92 and 100%, respectively. The latex-agglutination is a simple and rapid test; it can be used for retrospective diagnostics of the disease and determination of the titer of antibodies to the virus under conditions of a veterinary laboratory and even a fish farm.